ANALISIS KEGIATAN PRESERVASI PREVENTIF ARSIP DI KANTOR PERWAKILAN BANK INDONESIA PROVINSI SUMATERA BARAT - Elsa Oktaviani; Armida Silvia; Menik Kurnia Siwi (Jurnal Ecogen, 2018)
This research aims to analyze the preservation of archive prevention activities, the obstacles faced in the preservation of archive preventive activities as well as standard procedures for the implementation of archive preventive preservation activities conducted at the Representative Office of Bank Indonesia Prov. West Sumatra. This research method is descriptive qualitative, with source data some key informant through result of interview and direct observation to research object. The secondary data supporting this research were obtained from documents available at the site of the research object. To test the validity of data used Triangulation Technique. Based on information from informants of this study can be explained that archive preventive preservation activities as a whole have been done well and systematically. This can be seen in the presence of the Sentral Khasanah Archive (SKA) room equipped with adequate facilities and infrastructure. Implementation of fumigation done in per-riodik that is 2 times in a year which aims for early prevention activities to archive undamaged eaten by termites / damage to the archive because of the temperature and humidity factor of the room. Some of the obstacles that prevent optimum preservation of preservation in research object are caused by: 1) Human resources that have not background as archivist, 2) Low level of employee awareness, 3) Unavailability of special time for archive management. The results of this study also proves that the Standard Operating Procedures (SOP) used do not contain in detail the steps of preservation of archive preservation precautions. Key Words: Analysis, Preservation, and Preventive Archives